Comparison of game characteristics of male and female tennis players at Roland Garros 2005 - Filipcic, T.; Filipcic, A.; Berendijas, T. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2008)
The game characteristics of elite male and female tennis players at the French Open 2005 (Roland Garros) have been analyzed based on a large number of sets, a total of 894 in the category of men and 592 sets in the category of women. In addition, a comparison of game characteristics in an individual set between winners and losers has been made. It was ascertained that there are statistically characteristic differences in most variables between the winners and loser in the category of men as well as in the category of women. In the category of men, there are statistically characteristic differences in all variables except in the break point conversions. In women however, there are statistically characteristic differences in all variables except in the number of won aces. Based on these findings it can be concluded that statistically characteristic differences in the majority of variables, which define game characteristics, indicate that there are certain measurable indicators of tennis statistics, which distinguish winners from losers.